1994
DOI: 10.1002/art.1780371211
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of collagenase, stromelysin‐1, and timp‐1

Abstract: Objective. To measure serum levels of collagenase (MMP-l), stromelysin-1 (MMP3), and tissue inhibitor of matrix metalloproteinaise+l (TIMP-1) in normal subjects and in patients with osteoarthritis (OA), and to assess how these correlate with biochemical and clinical indicators of disease activity in OA.Methods. Specific iimmunoassays were used to measure MMPs, TIMP-1, and antigenic keratan sulfate (KS). The total area of cartilage affected by the disease was measured (expressed as an articular index).Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(22 citation statements)
references
References 40 publications
4
16
1
1
Order By: Relevance
“…A recent study demonstrated that serum TIMP-1 levels were significantly higher in patients with progressive RA over those who had radiographically stable disease [19]. These findings differed from previous studies, in which no association was observed between TIMP-1 levels and radiographic outcome [13,33,34]. In the context of our in vitro studies MMP-1, MMP-3 and TIMP-1 levels were elevated in response to IL-1β treatment.…”
Section: Discussioncontrasting
confidence: 95%
“…A recent study demonstrated that serum TIMP-1 levels were significantly higher in patients with progressive RA over those who had radiographically stable disease [19]. These findings differed from previous studies, in which no association was observed between TIMP-1 levels and radiographic outcome [13,33,34]. In the context of our in vitro studies MMP-1, MMP-3 and TIMP-1 levels were elevated in response to IL-1β treatment.…”
Section: Discussioncontrasting
confidence: 95%
“…In human studies, an elevated serum MMP-3 level has been observed in subjects with joint injury [23] and OA [24-26]; serum MMP-3 level may predict the rate of cartilage loss in an OA joint [27]. Interestingly, our results indicated that serum MMP-3 level decreased after intra-articular MMP-3 inhibitor treatment.…”
Section: Discussionmentioning
confidence: 53%
“…Экспери-ментальные данные свидетельствуют о том, что мРНК ММП1, 3 и 13 постоянно экспрессируются в суставном хряще [11]. Кроме того, ММП и продукты деградации аг-греканов присутствуют в синовиальной жидкости здоро-вых людей [12,13].…”
Section: таблицаunclassified